Edukasi Pengenalan Tokoh-Tokoh Pahlawan Nasional Indonesia Bagi Siswa Sekolah Dasar Di Kabupaten Kepulauan Yapen - Loppies, Megiridha; Aqil, Muhammad; Kulyasin; Febrianti, Sulja Mawar (J-Abdimas Cenderawasih, 2025)
The teaching of history at the elementary school level aims to establish a strong foundation for character development and the cultivation of national identity among students. In the 2024 Merdeka Belajar Curriculum, historical content integrated into the Natural and Social Sciences (IPAS) subject focuses on the study of family history, local community history, and the introduction of exemplary local figures. However, in the Yapen Islands Regency, the implementation of history education at the elementary level faces various challenges, including limited resources, a curriculum that lacks contextual relevance to the local environment, and inadequate educational facilities. In response to these issues, the community service program team initiated an educational activity designed to introduce national heroes to elementary school students in the region. The implementation of the program was divided into three stages: preparation, execution, and evaluation. The preparation stage involved the detailed drafting of the project proposal, the development of educational materials, and the organization of supporting resources and tools. The execution stage focused on delivering content about the roles of national heroes and engaging students through educational puzzle games specifically designed to enhance interactive learning and assessment. The evaluation stage was conducted to assess the effectiveness of the activities and to compile a comprehensive final report. The results demonstrated a significant positive impact, both in enhancing students’ historical knowledge and in fostering the values of heroism and nationalism, thereby offering an engaging and enjoyable alternative approach to history education for elementary school students